(untitled) (Transmediterranean History, 2021)
This article contextualises and analyses the account written by the monk of Saint-Gallen, Notker Balbulus, on the exchange of envoys between Charlemagne and the caliph of Baghdad that took place between 797–802. Notker’s embellished account was primarily concerned with entertaining and instructing Charlemagne’s great-grandson Charles III. The article examines this account on two level—the literary and the factual. This makes it possible to explore the obvious and the less obvious motivations of Charlemagne that set these extraordinary events in motion.